Prehospital Identification of Large Vessel Occlusions Using Modified National Institutes of Health Stroke Scale: A Pilot Study - Mulkerin, William D.; Spokoyny, Ilanit; Francisco, Jonathan T.; Lima, Brandon; Corry, Megan D.; Nudelman, Matthew J. R.; Niknam, Kian; Brown, Ian P.; Kohn, Michael A.; Govindarajan, Prasanthi (Frontiers in Neurology, 2021)
Stroke identification is a key step in acute ischemic stroke management. Our objectives were to prospectively examine the agreement between prehospital and hospital mNIHSS assessments as well as assess the prehospital performance characteristics of the Modified National Institute of Health Stroke Scale (mNIHSS) for identification of large vessel occlusion strokes. METHOD: In this prospective cohort study conducted over a 20-month period (11/2016 - 6/2018), we trained 40 prehospital providers (paramedics) in Emergency Neurological Life Support (ENLS) curriculum and in mNIHSS. English-speaking patients aged 18 and above transported for an acute neurological deficit were included. Using unique identifiers, we linked the prehospital assessment records to the hospital record. We calculated the agreement between prehospital and hospital mNIHSS scores using the Bland-Altman analysis and the sensitivity and specificity of the prehospital mNIHSS. RESULTS: Of the 31 patients, the mean difference (prehospital mNIHSS - hospital mNIHSS) was 2.4, 95% limits of agreement (-5.2 to 10.0); 10 patients (32%) met our a priori imaging definition of large vessel occlusion and the sensitivity of mNIHSS > 8 was 6/10 or 0.60 (95% CI 0.26 to 0.88) and the specificity was 13/21 or 0.62 (95% CI 0.38 to 0.82) respectively. CONCLUSIONS: We were able to train prehospital providers to use the prehospital mNIHSS. Prehospital and hospital mNIHSS had a reasonable level of agreement and and the scale was able to predict large vessel occlusions with moderate sensitivity.